Questions regarding the consolidation and division of criminal cases in the state of the coercion (Journal of actual problems of jurisprudence, 2018)
This article examines the legal rules governing the activities of prosecution bodies in the field of allocation and connection of criminal cases. Analyzes the problems arising in the implementation of pre-judicial investigation on these issues. Recommendations to improve the Criminal procedure code of RK. In modern society, is one of the urgent problems of the struggle with any crime. To date, this problem podlejit the ranks of the complex. Despite pirmiausia measures to likvidirovat actions of prestupnikov or stoped Nestan possible. To date, the code of criminal procedure the basics of the connection of criminal cases and the allocation of the criminal case does not settle. There are a number of challenges and gaps in addressing issues related vydeleniem and connection of criminal cases. Often they are directly related to procedural order connections and the allocation of criminal cases, calculation of time limits for preliminary investigation and inquiry, authority officials and the contradictions between the rules. Theissues raised by me, not yet defined by law. However, in the code of Criminal procedure of the Republicof Kazakhstan on the basis and procedure for connection of criminal cases and the allocation of criminalcases is much broader than the Criminal procedure code of the Kazakh SSR.Key words: court; pre-trial investigation of criminal cases, legal policy, the code of Criminal procedure,the Supreme Court, connection of criminal cases, the allocation of criminal cases.